A Single Case Study on the Impact of Ayurvedic Management on Tobacco (Nicotine) Addiction - Debaleena Acharjee; Deepak Thorat (Journal of Ayurveda, 2025)
Introduction: Almost 1 billion Indians are impacted by tobacco-related diseases every year. Gutka, a widely used smokeless tobacco, is linked to oral cancers, mucosal damage, and systemic health issues. This case study explores Ayurvedic management’s effectiveness in alleviating withdrawal symptoms and promoting long-term tobacco cessation. Main Clinical Findings: In this case a male patient presented with oral mucosal erythema, ulcers, constipation, anorexia, and indigestion for 15 days. He had a long-standing Gutka (tobacco) addiction and had experienced withdrawal symptoms – body aches, constipation, headache, anxiety, stress – during prior cessation attempts. Diagnosis: Clinical history and symptoms confirmed Nicotine Dependence Syndrome. Interventions: An Ayurvedic regimen was administered, including formulations like Deepana-pachana yoga, Medhya yoga, Ashwagandha Churna, Triphaladi Gandusha, and Khadiradi Gutika. Supportive measures included Padanshika Krama (gradual withdrawal), weekly counseling for the patient and family, and daily yoga for 1 month. Outcome: The intervention successfully relieved all symptoms and withdrawal effects. No relapse was observed even after tapering the treatment. Conclusions: This case study reports effective management of Nicotine addiction with Ayurvedic treatment solely with no relapse of symptoms.